2008
DOI: 10.1080/10668920701884414
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attributions for Success or Failure of Students in College Algebra

Abstract: Research in the field of attribution theory and academic achievement suggests a relationship between a student's attributional style and achievement. Theorists and researchers contend that attributions influence individual reactions to success and failure. They also report that individuals use attributions to explain and justify their performance. Studies in mathematics education identify attribution theory as the theoretical orientation most suited to explain academic performance in mathematics. This study fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…In [2], Bell et al, discuss national and local educational policies regarding College Algebra. In [3], Cortés-Suárez and Sandiford publish the findings of their study focused on the relationship among a high-risk course, low success rates, and attribution by examining the difference in the attributions passing and failing students gave for their performance in College Algebra. In [5] and [15], De Lange and Paulos, respectively, make a case for the importance of mathematical literacy in society.…”
Section: Related Workmentioning
confidence: 98%
“…In [2], Bell et al, discuss national and local educational policies regarding College Algebra. In [3], Cortés-Suárez and Sandiford publish the findings of their study focused on the relationship among a high-risk course, low success rates, and attribution by examining the difference in the attributions passing and failing students gave for their performance in College Algebra. In [5] and [15], De Lange and Paulos, respectively, make a case for the importance of mathematical literacy in society.…”
Section: Related Workmentioning
confidence: 98%
“…Research in this area has also shown a positive link between academic achievement and attribution style (Cortes-Suarez, 2005).…”
Section: Academic Achievement and Student Attributionsmentioning
confidence: 99%
“…According to the locus of causality of attribution theory, the former two fall within the external dimension, while the latter falls within the internal one. Attributing the choice to external causes shows self-serving or responsibility-shirking tendencies, while doing otherwise shows the tendency to take responsibility (Cortés-Suáres & Sandiford, 2008;Zhou, 2006;Weiner, 1985).…”
Section: Attributions For Studying In Ptementioning
confidence: 99%
“…Moreover, adding to the four main reasons that people like to give for their task outcomes (i.e., ability, effort, task difficulty, and luck) (Weiner, 1985), recent research cites such factors as intrinsic motivation, interest, needs, and mood (Chedzoy & Burden, 2007;Williams et al, 2004). Thus, the analysis of attributions serves the function of bringing self-relevant behavior into focus (Cortés-Suáres & Sandiford, 2008).…”
Section: Attributions For Studying In Ptementioning
confidence: 99%